24 hour blood pressure monitoring in healthy and hypertensive children. Issue 2 (February 1994) - Reusz, G S; Hóbor, M; Tulassay, T; Sallay, P; Miltényi, M
Abstract : 24 Hour ambulatory blood pressure monitoring (ABPM) was performed to provide data on the normal daily blood pressure of healthy schoolchildren and on patients with hypertension. The subjects studied were 123 healthy schoolchildren with a mean (SD) age of 12.5 (1.6) years (range 9.5-14.5 years), 24 children with borderline or mild hypertension, 17 with renal hypertension and normal renal function, 10 with chronic renal failure, and six with a renal allograft. In eight children with definite renal disease a second measurement was performed after treatment modification. The monitor used for ABPM was validated with a mercury column manometer. The mean (SD) of the signed differences of the blood pressure measured by the two methods was -0.19 (1.75) mmHg for the systolic and -0.21 (2.11) mmHg for the diastolic blood pressure (n = 60). Normal values for daytime and night time blood pressure were determined for those aged 10-14 years. The mean (SD) blood pressure of the 123 children was 109 (7)/66 (8) mmHg (systolic/diastolic) for the daytime and 96 (8)/52 (7) mmHg at night time. Of the 24 children with borderline or mild hypertension 14 had a raised blood pressure on ABPM. The circadian rhythm was disturbed in three children of this group. Even children with normal daytime blood pressure had significantly higher systolic blood pressure in the night when compared with the controls. The incidence of disturbed circadian rhythm was higher in the groups with renal hypertension (4/17 in the subgroup with normal renal function, 5/16 in the group with renal failure and/or transplantation). All children undergoing a second ABPM measurement had a lower average blood pressure after treatment adjustment. ABPM measurements were reproducible and accurate. The method provided new data on the physiological circadian variation of blood pressure in healthy children. It proved to be a helpful tool in the diagnosis of hypertension, particularly in the detection of cases of disturbance of the circadian rhythm of blood pressure pattern and individual adjustment of treatment.